Association between Sleep Apnea Hypopnea Syndrome and the Risk of Atrial Fibrillation: A Meta-Analysis of Cohort Study. (18th January 2018) - Zhao, Enfa; Chen, Shimin; Du, Yajuan; Zhang, Yushun
Abstract : Numerous reports have been done to seek the relationship between sleep apnea hypopnea syndrome (SAHS) and the risk of atrial fibrillation (AF). However, definite conclusion has not yet been fully established. We examined whether SAHS increases AF incidence in common population and summarized all existing studies in a meta-analysis. We summarized the current studies by searching related database for potential papers of the association between SAHS and the risk of AF. Studies that reported original data or relative risks (RRs) with 95% confidence intervals (CIs) for the associations were included. Sensitivity analyses were performed by omitting each study iteratively and publication bias was detected by Begg's tests. Eight eligible studies met the inclusion criteria. Fixed effects meta-analysis showed that SAHS increased AF risk in the common population (RR = 1.70, 95% CI: 1.53–1.89, P = 0.002, I 2 = 69.2 % ). There was a significant association between mild SAHS and the risk of AF (RR = 1.52, 95% CI: 1.28–1.79, P = 0.01, I 2 = 78.4 % ), moderate SAHS (RR = 1.88, 95% CI: 1.55–2.27, P = 0.017, I 2 = 75.6 % ), and severe SAHS (RR = 2.16, 95% CI: 1.78–2.62, P < 0.001, I 2 = 91.0 % ). The results suggest that sleep apnea hypopnea syndrome could increase the risk of AF, and the higher the severity of SAHS, the higher risk of atrial fibrillation.